A Multi-Level Multi-Agent Simulation Framework in Animal Epidemiology - Picault, Sébastien; Huang, Yu-Lin; Sicard, Vianney; Beaudeau, François; Ezanno, Pauline (Advances in Practical Applications of Cyber-Physical Multi-Agent Systems: The PAAMS Collection, 2017)
In order to recommend better control measures in public or animal health, epidemiologists incorporate ever-finer details in their models, from individual diversity to public policies, which often involve several observation scales. Due to the variety of modelling paradigms, it becomes more and more difficult to compare hypotheses and outcomes, all the more that the increased complexity of simulation programs is not yet counterbalanced by design principles nor by software engineering methods. We propose in this paper to use the multi-level agent-based paradigm to integrate existing methods within a common interface, provide a separation between concerns and reduce the part of code devoted to model designers. We illustrate our approach with an application to the Q fever disease in cattle.